Optical beamsteering using an 8 × 8 MEMS phased array with closed-loop interferometric phase control - Chan, Trevor K.; Megens, Mischa; Yoo, Byung-Wook; Wyras, John; Chang-Hasnain, Connie J.; Wu, Ming C.; Horsley, David A. (Optics express, 2013)
We present a high-speed optical beamsteering system based on an 8x8 MEMS phased array. The system incorporates an in situ interferometer that provides a real-time, dynamic measure of the phase of each mirror in the array during beamsteering. A closed-loop phase-control algorithm results in <π/100 mirror phase accuracy and far field beam steering is shown. Stroboscopic measurement capabilities are demonstrated which allow us to show feedforward control to eliminate micromirror ringing.